1990
DOI: 10.1128/iai.58.11.3689-3697.1990
|View full text |Cite
|
Sign up to set email alerts
|

Insertional inactivation of the gene encoding a 76-kilodalton cell surface polypeptide in Streptococcus gordonii Challis has a pleiotropic effect on cell surface composition and properties

Abstract: A library of Streptococcus gordonii DL1-Challis DNA was constructed in Agtll. Phage plaques were screened for production of antigens that reacted with antiserum to S. gordonii cell surface proteins. A recombinant phage denoted Agtll-cp2 was isolated that carried 1.85 kb of S. gordonu DNA and that expressed an antigen with a molecular mass of 29 kDa in Escherichia coli. Antibodies that reacted with the expression product were affinity purified and were shown to react with a single polypeptide antigen with a mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…(1 988). For haemagglutination assays, human type 0 erythrocytes in TBS-gelatin (Jenkinson and Easingwood, 1990) were mixed with dilutions of streptococcal cells in roundbottom microtitre plate wells, and incubated with shaking for 3 h at 20°C. Haemagglutination ability was recorded as the concentration of streptococcal cells per ml required to agglutinate 0.1% (vh) erythrocytes in a final volume of 0.1 ml.…”
Section: Adhesion Assays and Elsamentioning
confidence: 99%
“…(1 988). For haemagglutination assays, human type 0 erythrocytes in TBS-gelatin (Jenkinson and Easingwood, 1990) were mixed with dilutions of streptococcal cells in roundbottom microtitre plate wells, and incubated with shaking for 3 h at 20°C. Haemagglutination ability was recorded as the concentration of streptococcal cells per ml required to agglutinate 0.1% (vh) erythrocytes in a final volume of 0.1 ml.…”
Section: Adhesion Assays and Elsamentioning
confidence: 99%
“…(1993), Proteins were separated by SDS-PAGE on 8% (w/v) gels and were stained with silver nitrate (Morrissey, 1981) or with Coomassie brilliant blue. Proteins were transferred from polyacrylamide gels to Hybond-C nitrocellulose membrane {Amersham) by eleclrobiotting in 25 mM Tris, 192 mM glycine, 20% (v/v) methanol (Towbin et al.-1979) at 20 V cm " ' for 90min, Immunoblots were incubated with antiserum diluted 1:500 and antibody binding was detected using peroxidase-conjugated swine immunoglobuiins to rabbit immunoglobulin G, as described by Jenkinson and Easingwood (1990).…”
Section: Analysis Of Bacterial Proteinsmentioning
confidence: 99%
“…In Streptococcus gordonii, several cell-surface poiypeptides have been identified that appear to be involved in adhesion and colonization. SarA (76 kDa) in S. gordonii DL1 is a lipoprotein (Jeni<inson, 1992) involved in determining cell-aggregation properties, in particular with oral Actinomyces (Jenkinson and Easingwood, 1990). ScaA (38 kDa) in S. gordonii PK488 is aiso a iipoprotein (Andersen et ai, 1993) and is associated with the coaggregation of S. gordonii with Actinomyces naeslundii.…”
Section: Introductionmentioning
confidence: 99%
“…Several cell surface proteins have been implicated in adherence, hydrophobicity and aggregation reactions in S, gordonii (Jenkinson, 1986;1987;Jenkinson and Easingwood, 1990). Mutants with either reduced or increased cell-surface hydrophobicity were isolated following ethylmethane sulphonate mutagenesis of S. gordonii (Jenkinson and Carter, 1988).…”
Section: Introductionmentioning
confidence: 99%